A comunidade Camponesa do Salgado no contexto da territorialização do capital em Quirinópolis – GO - Santos, Hellen Cristina dos (2012)
This research analyzes the Community of Salt municipality Quirinópolis-GO, in the context of territorial disputes resulting from the process of Territorialization Capital. The result emphasized territorial dynamics, the use of biotechnological knowledge in the production of milk and its interference with the traditional knowledge of farmers Salgado, Agrobiodiversity and knowledge in the subjects who work in it, and finally she points out elements that indicate the power of resistance community in the face of actions taken by hegemonic actors involved in the Capital on Territorialization Quirinópolis. The incorporation of knowledge on biotech production constitutes an alternative to the permanence of the peasant on his estate, giving new meaning to their traditional knowledge. This research fits into the context of an effort by the Center for Studies and Research in Agricultural Geography and Territorial Dynamics - NEPAT in draft a territorial approach Cerrado, which seeks to understand the integration of different actors in territorial disputes. Understanding the cerrado, as territory, in all its facets requires analysis of the complexity of the actions taken by the actors and territorial decades. The qualitative research is conducted by the bias of the case study. To obtain the data were used secondary sources and field surveys in five visits to the community; resulted from these elements that provided an understanding of the actions of the different actors involved directly or indirectly in the community, among them, the plants installed in the city, representing the hegemonic actors, companies and cooperatives, which represent the regional actors and local actors, represented by the leaders of the community and municipal government. The Community of Salgado has not yet been incorporated into the production of cane sugar for the sugar and alcohol sector, due to its emphasis a bit more rugged and its soil conditions, but is engaged by the actions of the Ethanol industry, which is leading to changes in livelihoods of producers. Among these changes are the problems such as the decrease of the water level of the rivers, the deterioration of the roads used for the transportation of production, deforestation, biodiversity loss, lack of skilled labor that is concentrated in crops and sugarcane industries of this sector, the loss of the amount of students in the school, the lack of political support. We also emphasize the damage caused by the use of poisons in ace combat pests in the cane fields, they reach the community affecting cattle, pasture and quality of life of residents. Another important issue was the emergence of the stable fly, which proliferates in the cane fields because of the use of vinasse for fertilization, hence infests cattle community, causing irritation, mastitis, weight loss and consequently reduction of milk production. The factors presented throughout the text reinforce the current issues surrounding the use of the cerrado. Territorial disputes intensified by the game's global economy and mediated by several actors encounter resistance in local communities, to the extent that these shares to resume their innovation practices and strengthen their relationships.